Data collected at time of tagging Generation 1 catla (2022) and Generation 2 silver carp (2022) - Hamilton, Matthew G.; Akhter, Md; Roy, Aashish Kumar; Sarkar, Uzzal Kumar; Kundu, Ramprosad; Rahman, Md. Mustafizur; Shanta, Sirajum Monira; Kamruzzaman, Md.; Hossain, Jamal; Hossain, Mohammed; Haque, Mojammel; Sarkar, Anutosh; et al. (WorldFish, 2022)
Data collected at time of tagging G1 catla (2022) and G2 silver carp (2022) - WorldFish Carp Genetic Improvement Program